The double almost-Riordan group - He, Tian-Xiao (Linear algebra and its applications, 2025)
In this paper, we define double almost-Riordan arrays and find that the set of all double almost-Riordan arrays forms a group, called the double almost-Riordan group. We also obtain the sequence characteristics of double almost-Riordan arrays and give the production matrices of two types for double almost-Riordan arrays. In addition, we discuss the algebraic properties of the double almost-Riordan group, and finally give the compression of double almost-Riordan arrays and their sequence characteristics.